Trits(Pyrazol-1-YL)methane metal complexes for catalytic mild oxidative functionalizations of alkanes, alkanes and ketones - Martins, Luisa (2015)
This work concerns recent advances (since 2005) in the oxidative functionalization of alkanes, alkenes and ketones, under mild conditions, catalyzed by homoscorpionate tris(pyrazol-1-yl)methane metal complexes. The main types of such homogeneous or supported catalysts are classified, and the critical analysis of the most efficient catalytic systems in the different reactions is presented. These reactions include the mild oxidation of alkanes (typically cyclohexane as a model substrate) with hydrogen peroxide (into alkyl hydroperoxides, alcohols, and ketones), the hydrocarboxylation of gaseous alkanes (with carbon monoxide and potassium peroxodisulfate) into the corresponding Cn+1 carboxylic acids, as well as the epoxidation of alkenes and the Baeyer-Villiger oxidation of linear and cyclic ketones with hydrogen peroxide into the corresponding esters and lactones. Effects of various reaction parameters are highlighted and the preferable requirements for a prospective homogeneous or supported C-scorpionate-M-based catalyst in oxidative transformations of those substrates are identified. (C) 2014 Elsevier B.V. All rights reserved.